Racjonalność pedagogiki – pedagogika racjonalna? - Leppert, Roman (Horyzonty Wychowania, 2009)
The subject of consideration for the author is the questionabout the rationality of pedagogy, the ways in which it is understood,justification for dealing with this characteristic of pedagogicalreflection. The point of departure is understanding rationalityas the characteristic of thinking or acting. The criticism that thischaracteristic has met in the past decades was characterized.Relating rationality to pedagogy understood as natural or discursiveknowledge of education (educating and teaching), thepremises we refer to when analyzing the problem of rationalityof this scientific discipline were presented.